(NmSTISLAW rOSTROPOWI^s - (Nt(B.(NgAJDAMOWI^s; (Ne(B.(NgUL_QNCs (NREDAKTORs ((NmOSKWAs (NkOMPOZITORs, 1969)
(NaWTOR NI W KOEJ MERE NE PRETENDUET NA IS^ERPTYWA@]IJ ANALIZ TWOR^ESKIH PRINCIPOW(B.s
Keywords: (NMONOGRAFIQs